Mitochondria Encoded Non-coding RNAs in Cell Physiology - Liu, Xu; Shan, Ge (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are the powerhouses of mammalian cells, which participate in series of metabolic processes and cellular events. Mitochondria have their own genomes, and it is generally acknowledged that human mitochondrial genome encodes 13 proteins, 2 rRNAs and 22 tRNAs. However, the complexity of mitochondria derived transcripts is just starting to be envisaged. Currently, there are at least 8 lncRNAs, some dsRNAs, various small RNAs, and hundreds of circRNAs known to be generated from mitochondrial genome. These non-coding RNAs either translocate into cytosol/nucleus or reside in mitochondria to play various biological functions. Here we present an overview of regulatory non-coding RNAs encoded by the mammalian mitochondria genome. For overall understandings of non-coding RNAs in mitochondrial function, a brief summarization of nuclear-encoded non-coding RNAs in mitochondria is also included. We discuss about roles of these non-coding RNAs in cellular physiology and the communication between mitochondria and the nucleus.